THE EFFECT OF ACETIC ACID ON PROPERTIES OF COCONUT SHELL FILLED LOW DENSITY POLYETHYLENE COMPOSITES - Z.H. Tengku Faisal; Faisal Amri; H. Salmah; Iqmal Tahir (Universitas Gadjah Mada, 2010)
Natural lignocellulosics have an outstanding potential as reinforcement in thermoplastics. Coconut shell is one of natural lignocellulosic material. In this study, coconut shell (CS) was use as filler in low density polyethylene (LDPE) composites. The effect of surface treatment of coconut shell (CS) with acetic acid (acetylation) on mechanical properties, thermal properties and morphology were studied. The acetylation treatment has improved the tensile strength, elongation at break and Young's modulus of LDPE/CS composites. Thermogravimetric analysis (TGA) results show that the acetylated composites has better thermal stability compared to untreated composites at 600 °C. Differential scanning calorimetry (DSC) analysis showed that the esterification treatment increases the crystallinity of LDPE/CS composites. It was found that coconut shell acts as a nucleation agent in the presence of acrylic acid. The scanning electron microscopy (SEM) study of the tensile fracture surface of acetylated composites indicates that the presence of acetic acid increased the interfacial interaction.